Repertoire and Neutralizing Activity of Antibodies Against Hepatitis C Virus E2 Peptide in Patients With Spontaneous Resolution of Hepatitis C. (4th June 2019) - Olbrich, Anne; Wardemann, Hedda; Böhm, Stephan; Rother, Karen; Colpitts, Che C; Wrensch, Florian; Baumert, Thomas F; Berg, Thomas; Benckert, Julia
Abstract: Neutralizing antibodies can prevent hepatitis C virus (HCV) infection, one of the leading causes of cirrhosis and liver cancer. Here, we characterized the immunoglobulin repertoire of memory B-cell antibodies against a linear epitope in the central front layer of the HCV envelope (E2; amino acids 483–499) in patients who were infected in a single-source outbreak. A reverse transcription polymerase chain reaction–based immunoglobulin gene cloning and recombinant expression approach was used to express monoclonal antibodies from HCV E2 peptide–binding immunoglobulin G–positive memory B cells. We identified highly mutated antibodies with a neutralizing effect in vitro against different genotype isolates sharing similar gene features. Our data confirm the importance of VH 1–69 use for neutralizing activity. The data offer a promising basis for vaccine research and the use of anti-E2 antibodies as a means of passive immunization. Abstract : We identified 2 broadly neutralizing antibodies with shared genetic features directed against a central part of the β-sandwich of hepatitis C virus (HCV) E2 in patients with spontaneous resolution >30 years after HCV infection in a single-source outbreak.